Field recommended concentrations of pyraclostrobin exposure disturb the development and immune response of worker bees (Apis mellifera L.) larvae and pupae - Xiong, Manqiong; Qin, Gan; Wang, Lizhu; Wang, Ruyi; Zhou, Ruiqi; Luo, Xiaotian; Lou, Qun; Huang, Shaokang; Li, Jianghong; Duan, Xinle (Frontiers in Physiology, 2023)
The strobilurin fungicide pyraclostrobin is widely used to prevent and control the fungal diseases of various nectar and pollen plants. Honeybees also directly or indirectly contact this fungicide with a long-term exposure period. However, the effects of pyraclostrobin on the development and physiology of Apis mellifera larvae and pupae during continuous exposure have been rarely known. To investigate the effects of field-realistic concentrations of pyraclostrobin on honeybee survival and development, the 2-day-old larvae were continuously fed with different pyraclostrobin solutions (100 mg/L and 83.3 mg/L), and the expression of development-, nutrient-, and immune-related genes in larvae and pupae were examined. The results showed that two field-realistic concentrations of pyraclostrobin (100 and 83.3 mg/L) significantly decreased the survival and capped rate of larvae, the weight of pupae and newly emerged adults, and such decrease was a positive correlation to the treatment concentrations. qPCR results showed that pyraclostrobin could induce the expression of Usp, ILP2, Vg, Defensin1, and Hymenoptaecin, decrease the expression of Hex100, Apidaecin, and Abaecin in larvae, could increase the expression of Ecr, Usp, Hex70b, Vg, Apidaecin, and Hymenoptaecin, and decreased the expression of ILP1, Hex100 and Defensin1in pupae. These results reflect pyraclostrobin could decrease nutrient metabolism, immune competence and seriously affect the development of honeybees. It should be used cautiously in agricultural practices, especially in the process of bee pollination.